The affecting factors of willingness to communicate of inside classroom, outside classroom, and digital setting on Japanese language students - Muliadi, Muliadi (Japanese Research on Linguistics, Literature, and Culture, 2022)
The present study investigates the variables believed to relate to and affect Japanese language students’ willingness to communicate in Japanese in online learning situations. This study was a quantitative study that used questionnaire data as the main data distributed through the Google Form platform. A total of 81 Japanese language students from three universities participated. The findings showed that anxiety negatively correlated with willingness to communicate inside the classroom. Meanwhile, self-rating and virtual intercultural experiences positively correlated with willingness to communicate inside the classroom, outside the classroom, and in digital settings. The regression analysis showed that language anxiety, self-rating, and virtual intercultural experiences variables had a minor effect on willingness to communicate inside the classroom (19%) and digital setting (22.5 %). The results of this study indicate that besides the factors of anxiety, self-rating, and virtual intercultural experience, other variables are considered to be more contributing to how Japanese language students have the will to communicate in the target language.